Personal Data Protection in the Era of Digital Transformation: Challenges and Solutions in the Indonesian Cyber Law Framework - Solikhah, Mar'atus (Politeknik Siber Cerdika Internasional, 2025)
Indonesia's rapid digital transformation has led to an increase in the use of electronic systems in various sectors, but has not been accompanied by adequate regulatory readiness and legal infrastructure to protect people's personal data. The rise of data leakage incidents shows the weakness of the national data protection system, both normatively and institutionally. This research aims to analyze the legal challenges in the implementation of Law No. 27 of 2022 on Personal Data Protection (UU PDP) and formulate normative solutions and policies that are adaptive to the development of digital technology. This research uses a normative legal approach with document analysis methods, statutory, conceptual, and comparative approaches. Data was collected through literature study, regulatory analysis, case studies, and semi-structured interviews with relevant experts. The results show that the implementation of the PDP Law still faces structural challenges, including the absence of an independent supervisory authority, regulatory disharmony between sectors, and low public digital literacy. In addition, regulations have not been responsive to technological developments such as big data and artificial intelligence that bring new dimensions to the risk of privacy violations. This research recommends strengthening supervisory institutions, harmonizing sectoral regulations, and increasing public education on personal data rights as strategic steps towards an effective and adaptive cyber legal system in Indonesia.